Increase in Activity and Learning Outcomes of Economy Class XI IPS 1 Semester Odds Through Method Snowball Throwing on Economic Subjects in SMA 8 Kediri Year 2015/2016: INCREASE IN ACTIVITY AND LEARNING OUTCOMES OF ECONOMY CLASS XI IPS 1 SEMESTER ODDS THROUGH METHOD SNOWBALL THROWING ON ECONOMIC SUBJECTS IN SMA 8 KEDIRI YEAR 2015/2016 - Sri Yueli Puswati (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2018)
This research is purpose to increase the actity andeconomy result study of grade XI IPS 1 Semester 1. Through by the method of snowball throwing learning in the economy lesson in SMA Negeri 8 academic year 2015/2016. By using the metod of snowball throwing hopefully students can reach the purpose of the activity and the economy lesson. The kind of this research is classroom action wich was conducted in two cycles. First cycle consist of twice meeting and the second cycle consist of once time meeting. Every cycle consist of four stages that is planning implementation, action, observation and reflection. The subject of research is the students of XI IPS 1 Semester 1 of SMA Negeri 8 Kediri with total number of students 22. The success indicator of this research if 76% students active in this and increase the result study in every cycles by post test and if 76% can reach minimum criteria of mastery learning (KKM) that is 76. The result study show by using snowball throwing method in XI IPS 1 semester 1, the students activities learning in eaeach indicator increase 19,17% from first cycle 60% to 79,17% in second cycle. The increase of completeness students result increase from first cycle with total number of students 11 (74%) to 16 students (84%) that can reach minimum criteria of mastery learning (KKM) in second cycle